Relationship between SDB and short-term outcome in Finnish ischemic stroke patients - Haula TM; Puustinen J; Takala M; Holm A (WILEY, 2022)
Objectives Presence of sleep-disordered breathing (SDB) affects negatively recovery from stroke. The aim of this study is to evaluate the relationships between sleep-disordered breathing (SDB) and outcome measures in Finnish stroke unit cohort: mRS, need of rehabilitation and hospitalization time. Material and Methods An observational longitudinal study consisted of 95 patients referred to the Stroke Unit of Satakunta Hospital District over a period of November 2013 to March 2016. Patients were tested for SDB within 72 hr from the hospital admission because of ischemic stroke or TIA. The patients underwent polysomnography with NOX T3 wireless recorder. Results There are 37% (n = 35) non-OSA patients, 20% (n = 19) of patients have mild obstructive sleep apnea (OSA) and 39% (n = 37) have moderate/severe OSA and 4% (n = 4) have CSA. Patients with OSA have higher proportion of disability scores of mRS 3-5 (38%) compared to non-OSA (11%) and mild OSA (5%) patients on registration day (mRS0), and the same trend is seen at hospital discharge 35% versus 9% and 5%. (p = .009). Proportion of patients with OSA who needed rehabilitation is 65% (n = 19) versus non-OSA patients 17.5% (n = 4) and mild OSA patients 17.5% (n = 4;p = .039). We observed longer duration of hospitalization (5-15 days) in 29% of OSA patients compared to mild OSA patients 47% and OSA patients 54%. (p = .045). Conclusion Ischemic stroke patients with OSA have higher disability, higher need of rehabilitation, and longer hospitalization length. Prescreening tools for recognizing these stroke patients in acute phase could be valuable. That could result in earlier initiation of treatment and might prevent worse recovery from stroke.